Carbon footprint of food waste management options in the waste hierarchy – a Swedish case study. (15th April 2015) - Eriksson, Mattias; Strid, Ingrid; Hansson, Per-Anders
Abstract: Food waste is a problem with economic, environmental and social implications, making it both important and complex. Previous studies have addressed food waste management options at the less prioritised end of the waste hierarchy, but information on more prioritised levels is also needed when selecting the best available waste management options. Investigating the global warming potential of different waste management options offers a limited perspective, but is still important for validating generations from the waste hierarchy in a local context. This study compared the effect on greenhouse gas emissions of different food waste management scenarios representing different levels in the waste hierarchy in the city of Uppsala, Sweden. A life cycle assessment was performed for six waste management scenarios (landfill, incineration, composting, anaerobic digestion, animal feed and donations), using five food products (bananas, grilled chicken, lettuce, beef and bread) as examples when treated as individual waste streams. For all five waste streams, the established waste hierarchy was a useful, but approximate, tool for prioritising the various options, since landfill proved to be the worst option and donation, anaerobic digestion and incineration with energy recovery the best options, for easily handle products, wet products and dry products, respectively, taking into account the GHG emissions. The greatest potential for reducing greenhouse gas emissions was in the bread waste stream, since bread is an energy-rich product with a relatively low carbon footprint, increasing the possibilities for replacing fossil energy carriers. Lettuce, with its high water content, had the least potential to reduce greenhouse gas emissions when the waste management method was changed. Waste valorisation measures should therefore focus on food products with the potential to replace production of goods and services, rather than on food products that are wasted in large quantities or have a high carbon footprint. Highlights: Five individual waste streams from supermarkets in Uppsala, Sweden, were analysed. Six scenarios representing different levels in the waste hierarchy were investigated. Emissions of greenhouse gases were calculated using the life cycle assessment method. The waste hierarchy was found to be useful, but approximate, for waste management.